Contract bundling considerations in urban road project scheduling. (7th July 2021) - Miralinaghi, Mohammad; Davatgari, Amir; Seilabi, Sania E.; Labi, Samuel
Abstract: Road project scheduling and contract bundling are two separate concepts that profoundly influence project delivery consequences to key stakeholders. Therefore, agencies espouse initiatives for contract bundling (to reduce project costs) and project scheduling (to reduce user delay costs). Bundling combined with scheduling could potentially yield benefits to both the agency and urban road users. This paper investigates the overall benefits (to the two stakeholders) of optimal schedules with bundling considerations, compared to the optimal schedules for unbundled contracts. The agency's objective is to make scheduling‐with‐bundling decisions that minimize system‐wide travel time and project costs, and the users' objective is to minimize their travel times in the network with work zones. The problem is solved using the non‐dominated sorting genetic algorithm. The numerical experiments suggest that with well‐designed bundling, optimal scheduling can significantly reduce not only the project cost but also the total system cost (project and travel delay).